2011
DOI: 10.1186/1754-6834-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Arsenal of plant cell wall degrading enzymes reflects host preference among plant pathogenic fungi

Abstract: BackgroundThe discovery and development of novel plant cell wall degrading enzymes is a key step towards more efficient depolymerization of polysaccharides to fermentable sugars for the production of liquid transportation biofuels and other bioproducts. The industrial fungus Trichoderma reesei is known to be highly cellulolytic and is a major industrial microbial source for commercial cellulases, xylanases and other cell wall degrading enzymes. However, enzyme-prospecting research continues to identify opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
169
1
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(185 citation statements)
references
References 47 publications
9
169
1
6
Order By: Relevance
“…Variability in biomass conversion suggests that enzymatic pools are different following induction of the secretion of lignocellulose-acting enzymes due to genetic differences among the organisms. This feature was observed by King et al (17) and Russell et al (31). They indicate that after the identification of promising species, there is still significant variation among isolates which may reveal superior candidates.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Variability in biomass conversion suggests that enzymatic pools are different following induction of the secretion of lignocellulose-acting enzymes due to genetic differences among the organisms. This feature was observed by King et al (17) and Russell et al (31). They indicate that after the identification of promising species, there is still significant variation among isolates which may reveal superior candidates.…”
Section: Discussionsupporting
confidence: 69%
“…Recently, there has also been growing interest in the potential of plant-pathogenic fungi to optimize hydrolysis of lignocellulosic biomass (12). For instance, large-scale screening of ascomycetes revealed that the plant pathogens were more active than the nonpathogens on several lignocellulosic substrates (17).…”
Section: Discussionmentioning
confidence: 99%
“…Having been compiled from short-read data only, the C. higginsianum assembly is more fragmented than that of C. graminicola, resulting in some genes (5.2%) being split into two or more gene models, whereas others (4%) are truncated versions of the complete gene (Supplementary Note). After correcting for this fragmentation, the estimated gene content of C. higginsianum (15,331) is still markedly larger than that of C. graminicola. The two species share 9,795 orthologous genes.…”
Section: E T T E R Smentioning
confidence: 97%
“…A central challenge in the utilization of this material is its enzymatic conversion into fermentable sugars [3,4]. In this context, saprophytic and phytopathogenic fungi are known to coordinately produce, or to have the capacity to produce, a wide spectrum of lignocellulosic enzymes that can synergistically degrade structural polysaccharides in plant cell walls [5][6][7][8][9][10][11]. Filamentous fungi are also attractive expression hosts for recombinant protein production, especially due to their high enzyme secretory capacity [12][13][14].…”
Section: Introductionmentioning
confidence: 99%